2017
DOI: 10.1016/j.colsurfb.2017.04.029
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and characterization of poly(propylene imine)-dendrimer-grafted gold nanoparticles as nanocarriers of doxorubicin

Abstract: The aim of current work is synthesis 4th-generation-poly(propylene imine) (PPI)-dendrimer modified gold nanoparticles (Au-G4A) as nanocarriers for doxorubicin (DOX) and studying in vitro drug release kinetics from nanocarriers into different media. Accordingly, AuNPs were synthesized by reduction of chloroauric acid (HAuCl) aqueous solution with trisodium citrate and modified with cysteamine to obtain amine-functionalized (Au-NH) nanoparticles. Au-NH nanoparticles were used as multifunctional cores and partici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 53 publications
(16 citation statements)
references
References 42 publications
1
14
0
Order By: Relevance
“…32 These results collectively suggested that MoS 2 /GO nanocomposites possessed greatly enforced drug loading capacity than individual MoS 2 and GO, suggesting enhanced tumor-killing capability for MoS 2 /GO composites. It is worth noting that our MoS 2 /GO nanocomposites even showed greater DOX loading capacity when comparing with other mainstream nanomaterials reported previously, including PEGylated MoS 2 nanosheets, 28 PEGylated GO nanosheets, 57 poly(propylene imine)-dendrimer-grafted gold nanoparticles 58 and FA-conjugated polydopamine-modified mesoporous silica nanoparticles. 59 With respect to the mechanisms underlying DOX-loading onto MoS 2 /GO nanocomposites, at least three interactions are involved.…”
Section: Preferential Lung Accumulation Of Mos 2 /Go Nanocompositessupporting
confidence: 51%
“…32 These results collectively suggested that MoS 2 /GO nanocomposites possessed greatly enforced drug loading capacity than individual MoS 2 and GO, suggesting enhanced tumor-killing capability for MoS 2 /GO composites. It is worth noting that our MoS 2 /GO nanocomposites even showed greater DOX loading capacity when comparing with other mainstream nanomaterials reported previously, including PEGylated MoS 2 nanosheets, 28 PEGylated GO nanosheets, 57 poly(propylene imine)-dendrimer-grafted gold nanoparticles 58 and FA-conjugated polydopamine-modified mesoporous silica nanoparticles. 59 With respect to the mechanisms underlying DOX-loading onto MoS 2 /GO nanocomposites, at least three interactions are involved.…”
Section: Preferential Lung Accumulation Of Mos 2 /Go Nanocompositessupporting
confidence: 51%
“…To study the effect of these modification processes on SPR of AuNPs, UV–visible spectra of AuNPs and modified AuNPs were collected between 400 and 1100 nm as shown in Figure . Colloidal AuNPs show a narrow peak centred at 524 nm that indicates formation of stable AuNPs with diameter of 27.8 nm according to equation (1) : d=2.99λmax1539 where d (nm) and λ max (nm) are the diameter of nanoparticles and wavelength of absorption peak, respectively. Position and shape of the SPR band depend on the size and form of particles, as well as on the surrounding medium .…”
Section: Resultsmentioning
confidence: 99%
“…In recent decades, one of the most interesting fields in nanoscience has been metallic nanoparticles such as iron oxide, silver, gold, etc. Gold nanoparticles (AuNPs) are colloidal and stable ones widely employed in contemporary nanoscience applications such as chemical and biological sensing, medical diagnostics and therapeutics and biological imaging because of their strong surface plasmon resonance (SPR) absorption band in the visible region .…”
Section: Introductionmentioning
confidence: 99%
“…This unique macromolecules are made up of three basic parts including core that has at least two identical chemical functions, branches those are exuding from the core, and end functional groups those have important role in determining the properties of dendrimers (Fukushima, Hossain Sk, Sakamoto, Nakase, & Kojima, ; Samadaei, Salami‐Kalajahi, & Roghani‐Mamaqani, ). Until now, several types of dendrimers have been synthesized including polyamidoamine (PAMAM) dendrimer (Agarwal, Rustagi, Das, & Maiti, ; Samadaei, Salami‐Kalajahi, Roghani‐Mamaqani, & Banaei, ), poly(propylene imine) (PPI) dendrimer (Golshan, Salami‐Kalajahi, Roghani‐Mamaqani, & Mohammadi, ), chiral dendrimers (Ghorai, Bhattacharyya, & Bhattacharjya, ), tecto‐dendrimers (Schilrreff, Mundina‐Weilenmann, Romero, & Morilla, ), hybrid dendrimer structures (Golshan, Salami‐Kalajahi, Mirshekarpour, Roghani‐Mamaqani, & Mohammadi, ; Najafi, Salami‐Kalajahi, Roghani‐Mamaqani, & Kahaie‐Khosrowshahi, ), peptide dendrimer (Darbre & Reymond, ), glycodendrimers (Oliveira, Salgado, Sousa, Mano, & Reis, ), and so on. Unique properties of dendrimers such as high branching, water solubility, monodispersity, and their internal cavities lead to their applications in biological and drug application (Golshan, Salami‐Kalajahi, Roghani‐Mamaqani, & Mohammadi, ; He et al, ; Hu, Wang, He, & Gao, ; Kesharwani et al, ).…”
Section: Introductionmentioning
confidence: 99%